Improving The Quality Of Public Services Based On The Marriage Management Information System (Simkah) At The Muara Enim District Religious Affairs Office - Hardiyansyah Hardiyansyah; Nurnianah Nurnianah; Ivan Batara (UNIVED Press, 2024)
The research entitled Improving the Quality of Public Services Based on Marriage Management Information Systems (SIMKAH) in the Religious Affairs Office of Muara Enim District aims to identify and analyze the Application of Marriage Management Information Systems (SIMKAH) and its improvement in the quality of public services at the Office of Religious Affairs in Muara Enim District. This study uses qualitative research methods based on theories/opinions according to experts and existing literature.The results of the research show that the quality of services provided through the application of online SIMKAH has increased, this can be seen from the results of interviews with informants regarding the application and methods of using SIMKAH and the advantages offered by SIMKAH through the use of digital media.